THE CONCEPT OF STAFFING COURTS IN UKRAINE - Anastasiia Vynohradova (Journal of International Legal Communication, 2021)
The article is devoted to the formulation of the general definition of government authority and officials whose activities are aimed at staffing the courts, on this basis, proposals are given to improve the current administrative legislation. The research was performed using a systematic approach to staffing activities, taking into account the subject-object relationships that occur in the implementation of relevant activities. The characteristics of the objects of managerial influence as means of clarifying the competence of courts staffing subjects through the disclosure of their activity’s tasks. The essence and significance of the relevant connections in the implementation of courts staffing have been studied. Based on the peculiarities of the administrative and legal regulation of the staffing of the judiciary in connection with the characteristics of the subject of public administration, the general and specific features of a subject of courts staffing are identified. The specific features of these entities, due to the peculiarities of the judiciary as a sphere of their activities, include: staffing of courts, as a rule, is not the main direction of their activities (except for the HCJC of Ukraine and the National School of Judges of Ukraine); staffing of the court is carried out mainly by entities that are not included in the staff list of a particular court, and therefore has an external nature to the court (GRP, HCJC of Ukraine, President of Ukraine, SJA of Ukraine, National School of Judges of Ukraine, judicial self-government and others authorized entities); mostly collegial principles of decision-making. The definition of a subject of courts staffing is an authorized body of state power or its official, whose activities are aimed at ensuring the proper professional level of court officials, ensuring the ability of courts to effectively perform their tasks. The expediency of consideration of a subject of courts staffing in the narrow and broad senses is substantiated. It is pointed out that the current wording of item 6.2 of the Regulations on the procedure for election to and dismissal of the chairman, first deputy, deputy chairmen, and chairmen of judicial chambers of the Court of Appeal of 12.10.2001 is inconsistent with the current norms of Part 4 of Art. 20 of the Law of Ukraine “On the Judiciary and the Status of Judges” of 02.06.2016 № 1402-VIII, in connection with which proposals for amendments to the said Law.